Determination of Five Coumarins in Angelicae Pubescentis Radix from Different Origins by HPTLC-Scanning - Dangtong Ji; Qian Li; Hanting Yang; Yue Fan; Ting Wang; Yuying Chen (Journal of Analytical Methods in Chemistry)
The HPTLC method is widely used in the field of quality evaluation and component analysis of traditional Chinese medicine (TCM). This work developed an HPTLC method to determine the five effective components of osthole, columbianadin, isoimperatorin, oxypeucedanin, and imperatorin in Angelicae Pubescentis Radix (APR) from twelve different origins, and the quality difference was analyzed by comprehensive factor analysis and cluster analysis. The results showed that the calibration curves of five components exhibited good linearity within the linear ranges (0.8–4.0 μg). The RSD of precision was 1.06%–1.21%, and the repeatability and stability tests were good. The results of cluster analysis showed that the APR from 12 different areas was divided into two categories, and at the same time, it was found that the quality of Dazhou in Sichuan and Huating in Gansu was better than in other areas. In this study, a simple, rapid, and efficient method for quality evaluation of TCM was established by the HPTLC method.